La Pace Calda. La nascita del movimento antinucleare negli Stati Uniti e in Gran Bretagna, 1957-1963 - Fazzi, Dario <1982> (Alma Mater Studiorum - Università di Bologna, 2010)
The aim of this proposal is to offer an alternative perspective on the study of Cold War, since insufficient attention is usually paid to those organizations that mobilized against the development and proliferation of nuclear weapons. The antinuclear movement began to mobilize between the 1950s and the 1960s, when it finally gained the attention of public opinion, and helped to build a sort of global conscience about nuclear bombs. This was due to the activism of a significant part of the international scientific community, which offered powerful intellectual and political legitimization to the struggle, and to the combined actions of the scientific and organized protests. This antinuclear conscience is something we usually tend to consider as a fait accompli in contemporary world, but the question is to show its roots, and the way it influenced statesmen and political choices during the period of nuclear confrontation of the early Cold War. To understand what this conscience could be and how it should be defined, we have to look at the very meaning of the nuclear weapons that has deeply modified the sense of war. Nuclear weapons seemed to be able to destroy human beings everywhere with no realistic forms of control of the damages they could set off, and they represented the last resource in the wide range of means of mass destruction. Even if we tend to consider this idea fully rational and incontrovertible, it was not immediately born with the birth of nuclear weapons themselves. Or, better, not everyone in the world did immediately share it. Due to the particular climate of Cold War confrontation, deeply influenced by the persistence of realistic paradigms in international relations, British and U.S. governments looked at nuclear weapons simply as «a bullet». From the Trinity Test to the signature of the Limited Test Ban Treaty in 1963, many things happened that helped to shift this view upon nuclear weapons. First of all, more than ten years of scientific protests provided a more concerned knowledge about consequences of nuclear tests and about the use of nuclear weapons. Many scientists devoted their social activities to inform public opinion and policy-makers about the real significance of the power of the atom and the related danger for human beings. Secondly, some public figures, as physicists, philosophers, biologists, chemists, and so on, appealed directly to the human community to «leave the folly and face reality», publicly sponsoring the antinuclear conscience. Then, several organizations leaded by political, religious or radical individuals gave to this protests a formal structure. The Campaign for Nuclear Disarmament in Great Britain, as well as the National Committee for a Sane Nuclear Policy in the U.S., represented the voice of the masses against the attempts of governments to present nuclear arsenals as a fundamental part of the international equilibrium. Therefore, the antinuclear conscience could be defined as an opposite feeling to the development and the use of nuclear weapons, able to create a political issue oriented to the influence of military and foreign policies. Only taking into consideration the strength of this pressure, it seems possible to understand not only the beginning of nuclear negotiations, but also the reasons that permitted Cold War to remain cold.